Hubungan Koordinasi Mata dan Kaki serta Kekuatan Otot Tungkai terhadap Keterampilan Shooting ke Gawang Sepak Bola pada Pemain SSB Duri Galaxy U-17 - Adib Husein; Zainur Zainur; Oca Fernandes AF (Departement of Mathematics Education, 2023)
The game of football requires eye and foot coordination and the strength of a player's leg muscles when shooting a kick, because in carrying out shooting techniques towards the goal it must be well coordinated so that the ball goes right towards the opponent's goal and can score goals that can give victory. Therefore this study was conducted with the aim of knowing the relationship between eye and foot coordination and leg muscle strength on soccer shooting skills in SSB Duri Galaxy U-17 players. The type of research used is correlation, with data collection techniques using eye and foot coordination test instruments, leg muscle strength tests and soccer shooting tests. The data source in this study were 24 SSB Duri Galaxy U-17 players. Based on the results of the research that has been done, the following conclusions can be drawn: (1) There is a relationship between eye and foot coordination on shooting skills at goal soccer in SSB Duri Galaxy U-17 players with rcount = 0.520 > rtable = 0.404, (2 ) There is a relationship between leg muscle strength and shooting skills at goal soccer in SSB Duri Galaxy U-17 players with a value of rcount = 0.635 > rtable = 0.404, (3) There is a relationship between eye and foot coordination and leg muscle strength on goal shooting skills. ball on SSB Duri Galaxy U-17 players with a value of rcount = 0.639 > rtable = 0.404 which belongs to the Strong category because it lies in the interval between 0.60-0.799 in the correlation value category.